Amphotericin B Lipid Complex or Amphotericin B Multiple-Dose Administration to Rabbits with Elevated Plasma Cholesterol Levels: Pharmacokinetics in Plasma and Blood, Plasma Lipoprotein Levels, Distribution in Tissues, and Renal Toxicities - Ramaswamy, Manisha (American Society for Microbiology, 2001)
The purpose of the present study was to determine if a relationship exists between the plasma cholesterol concentration, the severity of amphotericin B (AmpB)-induced renal toxicity, and the pharmacokinetics of AmpB in plasma in hypercholesterolemic rabbits administered multiple doses of amphotericin B (AmB) deoxycholate (Doc-AmB) and AmB lipid complex (ABLC). After 7 days of administration of a cholesterol-enriched diet (0.50% [wt/vol]) or a regular rabbit diet, each rabbit was administered a single intravenous bolus of Doc-AmB (n = 8) or ABLC (n = 10) (1.0 mg/kg of body weight) daily for 7 consecutive days (a total of eight doses). Blood samples were obtained daily before and 24 h after the administration of each dose and serially thereafter following the administration of the last dose for the assessment of pharmacokinetics in plasma, kidney toxicity, plasma lipoprotein levels, and drug distribution in tissue. The pharmacokinetics of AmB in blood following the administration of ABLC were also determined in rabbits fed cholesterol-enriched and regular diets (n = 3 each group). Before drug treatment, cholesterol-fed rabbits demonstrated marked increases in total, low-density lipoprotein (LDL), and triglyceride-rich lipoprotein (TRL) cholesterol levels in plasma compared with the levels in rabbits on a regular diet. No significant differences in total plasma triglyceride levels were observed. Significant increases in plasma creatinine levels were observed in rabbits fed a cholesterol-enriched diet (P < 0.05) and rabbits fed a regular diet (P < 0.05) when administered AmB. However, the magnitude of this increase was twofold greater in rabbits fed a regular diet than in rabbits fed a cholesterol-enriched diet. An increase in plasma creatinine levels was observed only in rabbits on a cholesterol-enriched diet administered ABLC. The pharmacokinetics of AmB were significantly altered in rabbits on a cholesterol-enriched diet administered Doc-AmB or ABLC compared to those in rabbits on a regular diet administered each of these compounds. The pharmacokinetics of AmB in blood were significantly different following ABLC administration but not following Doc-AmB administration in both rabbits fed cholesterol-enriched diets and rabbits fed regular diets compared to their corresponding pharmacokinetics in plasma. An increased percentage of AmB was recovered in the TRL fraction when Doc-AmB was administered to rabbits fed a cholesterol-enriched diet than when it was administered to rabbits fed a regular diet. Furthermore, an increased percentage of AmB was recovered in the LDL and TRL fractions when ABLC was administered to rabbits fed a cholesterol-enriched diet rabbits fed a regular diet. These findings suggest that an increase in plasma cholesterol levels modifies the pharmacokinetics of AmB and renal toxicity following the administration of multiple intravenous doses of Doc-AmB and ABLC.